2022
DOI: 10.37641/jiakes.v10i2.1330
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor yang Mempengaruhi Tax Avoidance Perusahaan Perbankan

Abstract: This study aims to examine the effect of the Audit Committee, Independent Commissioner, Company Size, Leverage, and Liquidity on Tax Avoidance in banking sector companies listed on the Indonesia Stock Exchange during the 2017-2020 period. The type of research used is quantitative research using secondary data sources obtained from annual financial reports on the Indonesia Stock Exchange (IDX). The sampling technique in this study used purposive sampling method and obtained 41 companies from a total of 164 obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
3
4
1
Order By: Relevance
“…So Ho is accepted, and Ha is rejected, meaning Leverage has no significant effect on Tax Avoidance. The research results differ from previous researchers Adinda Putri Puspitasari and Sartika Wulandari (2022), who stated that Leverage had a significant negative effect on Tax Avoidance. However, previous researchers Mustika Ningtyas and friends (2020) stated that Leverage has no significant effect on Tax Avoidance.…”
Section: The Effect Of Leverage On Tax Avoidancecontrasting
confidence: 99%
See 1 more Smart Citation
“…So Ho is accepted, and Ha is rejected, meaning Leverage has no significant effect on Tax Avoidance. The research results differ from previous researchers Adinda Putri Puspitasari and Sartika Wulandari (2022), who stated that Leverage had a significant negative effect on Tax Avoidance. However, previous researchers Mustika Ningtyas and friends (2020) stated that Leverage has no significant effect on Tax Avoidance.…”
Section: The Effect Of Leverage On Tax Avoidancecontrasting
confidence: 99%
“…Based on the table above, it is shown that the significance value of 0.191 for the influence of Company Size on Tax Avoidance is 0.191 > 0.05, and the t value is -1.318 < table 1.99045, so Ho is accepted, and Ha is rejected, which means that Company Size has no significant effect on Tax Avoidance. These results are inversely proportional to previous researchers, Adinda Putri Puspitasari and Sartika Wulandari (2022), which showed a significant positive effect between company size and tax avoidance. However, in research, 2020 Muda et al, 2020 said that company size does not affect tax avoidance.…”
Section: The Influence Of Company Size On Tax Avoidancesupporting
confidence: 66%
“…The quantification of leverage is accomplished through the computation of the financial ratio that compares the debt to the capital of the company. Following that, the company uses this leverage to carry out its debt-financed operations (Puspitasari & Wulandari, 2022). Firms that exhibit high leverage ratios rely heavily on debt financing, while those with low leverage ratios are capable of self-financing their operations (Sari & Rahayu, 2020).…”
Section: Leveragementioning
confidence: 99%
“…The size of a business is indicative of its asset and resource basis, with larger businesses generating higher profits and correspondingly elevated tax liabilities. Typically, organizations with substantial resources have greater tax avoidance expertise (Puspitasari & Wulandari, 2022). According to Widyaningsih et al (2018), the size of a company has a substantial effect on tax reduction.…”
Section: The Impact Of Company Size On Tax Avoidancementioning
confidence: 99%
See 1 more Smart Citation